The Experiences of Intensive Care Nurses in Advocacy of COVID-19 Patients - Bahman Aghaie PhD (SAGE Publishing, 2021)
The lack of face-to-face interactions with families, the increase in the number of patients admitted to the ICU, nursing staff shortages, and inadequate personal protective equipment has created many challenges for nurses in advocacy of the COVID-19 patient with life-threatening conditions. This study aimed to explore the experiences of intensive care nurses in the advocacy of COVID-19 patients. This study was performed using a qualitative content analysis method with Graneheim and Lundman approach, Iran, 2020. Data were collected through semi-structured interviews with eighteen clinical nurses from the intensive care units of three hospitals. Themes extracted from the nurses’ statements were promoting patient safety (informing physicians about the complications and consequences of treatment, preventing medical errors, protecting patients from threats), respecting the patients’ values (providing comfort at the end of life, providing a comfortable environment, commitment to confidentiality, cultural observance, respect for individualism, fair care), and informing (clarifying clinical conditions, describing available services, and being the patients’ voice). ICU nurses in health crises such as COVID-19 as patient advocates should promote patient safety, respect patients’ values, and inform them. The results of this study could help enhance the active role of intensive care nurses in the advocacy of COVID-19 patients.